Synergy of e-science and libraries as a support to higher education institutions in Croatia - Vrana, Radovan (Array, 2013)
The paper presents an idea of expansion of the existing modes of collaboration between science with focus on e-science, libraries which services are currently going through a new phase of transformation into services based on use of federated digital information resources and finally, higher education system which seeks quality information resources for their use in the teaching process. All three sides have a historical background of mutual collaboration. Influence of information and communication technology on all three sides has sped up their development and provided them with new tools for creation, organization, storage and exchange of knowledge. All three sides still haven’t used a full potential of networked environment and internet services for the benefit of even richer collaboration and designing of new ICT supported services in science, libraries and teaching at higher education institutions that would enable richer scientific, library and educational experiences. The results of this collaboration should be network intensive collaboration based on selected and verified digital content of scientific provenance ; user tailored networked services in libraries and innovative forms of teaching at universities.